A novel conditional Aire allele enables cell-specific ablation of the immune tolerance regulator Aire - Dobeš, Jan; Edenhofer, Frank; Vobořil, Matouš; Brabec, Tomáš; Dobešová, Martina; Čepková, Adéla; Klein, Ludger; Rajewsky, Klaus; Filipp, Dominik (European journal of immunology, 2018)
Medullary thymic epithelial cell (mTEC)-restricted expression of autoimmune regulator (Aire) is essential for establishment of immune tolerance. Recently, Aire was also shown to be expressed in cells of hematopietic and reproductive lineages. Thus, the generation of Airefl/fl mouse strain enables the investigation of the cell-specific function of Aire.
Keywords: Reproduction; Humans; rozmnožování; buněčný rodokmen; Mice, Transgenic; Transcription Factors; Conditional knockout; Female; Immune Tolerance; Aire; myši transgenní; Antigen-Presenting Cells; lidé; zvířata; myši; AIRE Protein; Cell Lineage; Immune tolerance; Mice; myši knockoutované; ženské pohlaví; Male; Mice, Knockout; imunologická tolerance; autoimunitní polyglandulární syndromy; Medullary thymic epithelial cells; transkripční faktory; Animals; antigen prezentující buňky; mužské pohlaví; protein AIRE; Polyendocrinopathies, Autoimmune